PD-L1 SNPs as biomarkers to define benefit in patients with advanced NSCLC treated with immune checkpoint inhibitors. Issue 1 (February 2022) - Minari, Roberta; Bonatti, Francesco; Mazzaschi, Giulia; Dodi, Alessandra; Facchinetti, Francesco; Gelsomino, Francesco; Cinquegrani, Gloria; Squadrilli, Anna; Bordi, Paola; Buti, Sebastiano; Bersanelli, Melissa; Leonetti, Alessandro; et al.
Objective: To investigate the role of CTLA-4, PD-1 (programmed death-1), and PD-L1 (programmed death-ligand 1) single nucleotide polymorphisms (SNPs) in predicting clinical outcome of patients with advanced non-small cell lung cancer (NSCLC) treated with immune checkpoint inhibitors (ICIs). Methods: A total of 166 consecutive patients were included. We correlated SNPs with clinical benefit, progression-free survival, time to treatment failure, and overall survival and evaluated the incidence of SNPs in nonresponder and long clinical benefit groups. Results: Considering the entire cohort, no correlation was found between SNPs and clinical outcome; however, PD-L1 rs4143815 SNP and the long clinical benefit group showed a statistically significant association ( p = 0.02). The nonresponder cohort displayed distinctive PD-L1 haplotype ( p = 0.05). Conclusion: PD-L1 SNPs seem to be marginally involved in predicting clinical outcome of NSCLC treated with ICI, but further investigations are required.